The Influence of Regional Expenditure, Labor, and the Poor on South Sulawesi's GDP - Rajab, Abdul (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study is a study that aims to determine the influence of regional spending, labor, and the poor on South Sulawesi's GDP simultaneously and partially. This study is a quantitative research using secondary data from the last 10 years of time series with BPS data sources. The results of the study show that simultaneously shows that there is an influence simultaneously or together where the variables X1 (regional spending), X2 (labor), and X3 (poor population) on Y (GDP) of South Sulawesi Province. In a partial test based on the significance value that has a significant influence, only the X2 variable (labor), while the other variables, namely X1 (regional spending) and X3 (poor population), do not have a significant influence. For the results of the partial test based on the calculation value and the table, it was concluded that X1 had no effect, which meant that the increase in the regional expenditure variable did not affect the increase in the GDP of South Sulawesi Province, then for the X2 variable had a positive effect, which meant that the increase in the labor variable would affect the increase in the GDP of South Sulawesi Province and for the X3 variable had a negative effect, which meant that the increase in the poor variable could affect the decrease in the GDP of Sulawesi Province South